MARKETING ANALYSIS OF NASI TERI FISH PRODUCTS: Case Study of Terapung Village, Mawasangka District, Central Buton Regency - Muhammad Zainal; Ine Fausayana; Wa Ode Yusria (International journal of technology and education research, 2024)
This research aims to determine income, marketing channels and marketing efficiency in Floating Village, Mawasangka District, Central Buton Regency. The research location was determined using purposive sampling with the consideration that the area is an anchovy producer. This research was carried out in February - July, the sample determination in this research was carried out using a non-probabilistic sampling method with a purposive sampling method with certain criteria. Data analysis in this research uses descriptive analysis, income analysis and marketing efficiency analysis. The research results show that in the research area, the income from each anchovy processor averages IDR 28,190/Kg and there is only one channel pattern and a marketing efficiency level of 2%, which is in the efficient category